The changing pattern of enteric pathogen infections in China during the COVID-19 pandemic: a nation-wide observational study - Li-Ping Wang; Jia-Yi Han; Shi-Xia Zhou; Lin-Jie Yu; Qing-Bin Lu; Xiao-Ai Zhang; Hai-Yang Zhang; Xiang Ren; Cui-Hong Zhang; Yi-Fei Wang; Sheng-Hong Lin; Qiang Xu; et al. (Elsevier, 2021)
Background: Non pharmaceutical interventions (NPI) including hand washing directives were implemented in China and worldwide to combat the COVID-19 pandemic, which are likely to have had impacted a broad spectrum of enteric pathogen infections. Methods: Etiologically diagnostic data from 45 937 and 67 395 patients with acute diarrhea between 2012 and 2020, who were tested for seven viral pathogens and 13 bacteria respectively, were analyzed to assess the changes of enteric pathogen infections in China during the first COVID-19 pandemic year compared to pre-pandemic years. Findings: Test positive rates of all enteric viruses decreased during 2020, compared to the average levels during 2012−2019, with a relative decrease of 71•75% for adenovirus, 58•76% for norovirus, 53•50% for rotavirus A, and 72•07% for the combination of other four uncommon viruses. In general, a larger reduction of positive rate in viruses was seen among adults than pediatric patients. A rebound of rotavirus A was seen after September 2020 in North China rather than South China. Test positive rates of bacteria decreased during 2020, compared to the average levels during 2012−2019, excepting for nontyphoidal Salmonella and Campylobacter coli with 66•53% and 90•48% increase respectively. This increase was larger for pediatric patients than for adult patients. Interpretation: The activity of enteric pathogens changed profoundly alongside the NPIs implemented during the COVID-19 pandemic in China. Greater reductions of the test positive rates were found for almost all enteric viruses than for bacteria among acute diarrhea patients, with further large differences by age and geography. Lifting of NPIs will lead to resurgence of enteric pathogen infections, particularly in children whose immunity may not have been developed and/or waned. Funding: China Mega-Project on Infectious Disease Prevention; National Natural Science Funds.